Imbalance in Prehypertension Effect on the Myocardial Works for the Student of Medical College - Ibrahim, Ibrahim T (Diyala Journal of Medicine, 2019)
Background: Imbalance in prehypertension represent one of the mean causes that effect in the myocardial work loud and causes stress on heart in different position for both gender in different ages healthy or non-healthy this study healthy young male and female student in the college of medicine as a volunteers. Objective: To study the effect of stress during the lecture on the heart for female and male in both position sitting and standing. Patients and Methods: 20 healthy looking medical students of age between 23-24 years old of both genders were participated in the study they are divided in two group male and female with standing and sitting position. Results Correlation between the heart rate in sitting position and heart rate in the standing position as it is seen there are an increasing in both sitting and standing , R2= (0.3356) significant in standing .R2=( 0.1149) also significant in the sitting. Conclusion: Find from this study that female total value increase on the sitting and standing position where male decrease in both positions.